2014
DOI: 10.1080/00207160.2014.915957
|View full text |Cite
|
Sign up to set email alerts
|

A novel logistic multi-class supervised classification model based on multi-fractal spectrum parameters for hyperspectral data

Abstract: A novel logistic multi-class supervised classification model based on multi-fractal spectrum parameters is proposed to avoid the error that is caused by the difference between the real data distribution and the hypothetic Gaussian distribution and avoid the computational burden working in the logistic regression classification directly for hyperspectral data. The multi-fractal spectra and parameters are calculated firstly with training samples along the spectral dimension of hyperspectral data. Secondly, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…More precisely, Combrexelle et al [30] calculated coefficients of the polynomial describing the multifractal spectrum for each spectral band. Li et al in [42] showed that using multifractal parameters for spectral profiles' description may improve the average accuracy by 7-8%. Incorporation of multifractal parameters resulted in higher overall accuracy (almost 10%) in the algorithm proposed by Wan et al [43].…”
Section: Multifractalsmentioning
confidence: 99%
“…More precisely, Combrexelle et al [30] calculated coefficients of the polynomial describing the multifractal spectrum for each spectral band. Li et al in [42] showed that using multifractal parameters for spectral profiles' description may improve the average accuracy by 7-8%. Incorporation of multifractal parameters resulted in higher overall accuracy (almost 10%) in the algorithm proposed by Wan et al [43].…”
Section: Multifractalsmentioning
confidence: 99%
“…Due to the powerful data acquisition and analysis capabilities, the hyperspectral technique is naturally applied in intelligent agriculture [3][4][5][6][7][8][9]. Nevertheless, since that the hyperspectral remote sensing has the characteristics of multi band, narrow band width and large amount of data, the analysis of dynamic structure of hyperspectral signal become a critical premise to promote its effective utilization [10][11][12]. One of the key pretreatment task is to detect information redundancy hidden in hyperspectral, which seriously affects the extraction of real information of spectrum [13].…”
Section: Introductionmentioning
confidence: 99%
“…A very challenging problem in the remote sensing community is to generate land-cover maps for semantically characterizing Earth's surface [1,2,3,4,5,6]. As one of the most widely used approaches, hyperspectral image (HSI) classification has recently gained in popularity and attracted research interests from other scientific disciplines such as image processing, machine learning, and computer vision [7,8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%